P3 Bézier CAD Surrogates for anisotropic mesh adaptation. (July 2023) - Loseille, Adrien; Rochery, Lucien
Abstract: Mesh generation and adaptation rely heavily on BREPs created by proprietary CAD software, piecewise parametric descriptions of geometry from which numerous problems arise: model continuity is only enforced up to a tolerance often higher than required mesh sizes, projection is costly and prone to error, derivatives – thus normals and surface curvatures – may not be well defined, unintended small features driving unnecessary mesh complexity may be present... High-order surface meshes can be used as a faster and more robust alternative, at a small expense of memory. P 3 meshes, in particular, are the first degree for which G 1 continuity at the vertices may be enforced while retaining degrees of freedom to improve geometric accuracy. In this paper, we exhibit the ability of these P 3 CAD surrogates to drive anisotropic surface adaptation in place of traditional CAD systems through the example of an adaptation loop using a highly anisotropic metric field on the complex geometry of the HL-CRM wing model with flaps. Graphical abstract: Highlights: BREPs present errors within tolerances too high for mesh adaptation in CFD P 3 surface meshes proposed as CAD surrogate in adaptation CAD surrogate error bounded by high-order surface approximation metric fields Metric fields and normals computed using CAD derivatives or estimations Simple P 3 surface smoothing schemes robustly provide accurate surrogate Projection and derivatives for adaptation more robust, faster, on CAD surrogate Ability to quickly produce P 3 surface meshes of complex geometries illustrated. Highly anisotropic metric-based adaptation using only CAD surrogate illustrated.